The Adult Adrenal Cortex Undergoes Rapid Tissue Renewal in a Sex-Specific Manner - Grabek, Anaëlle; Dolfi, Bastien; Klein, Bryan; Jian-Motamedi, Fariba; Chaboissier, Marie-Christine; Schedl, Andreas (Cell stem cell, 2019)
Evolution has resulted in profound differences between males and females that extend to non-reproductive organs and are reflected in the susceptibility and progression of diseases. However, the cellular and molecular basis for these differences remains largely unknown. Here we report that adrenal gland tissue renewal is highly active and sexually dimorphic, with female mice showing a 3-fold higher turnover than males. Moreover, in males, homeostasis relies on proliferation of cells within the steroidogenic zone, but females employ an additional stem and/or progenitor compartment situated in the adrenal capsule. Using lineage tracing, sex reversal models, gonadectomy, and dihydrotestosterone treatments, we further show that sex-specific stem cell activity is driven by male hormones that repress recruitment of Gli1+ stem cells from the capsule and cell proliferation. Taken together, our findings provide a molecular and cellular basis for adrenal sex dimorphism that may contribute to the increased incidence of adrenal diseases in females. [Display omitted] •The adult adrenal cortex is subject to extensive cell renewal•Tissue turnover of the adrenal cortex in females is 3 times higher than in males•Capsular stem cells contribute to adult cortex replenishment in females only•Dihydrotestosterone treatment in females abolishes capsular stem cell recruitment Evidence in both mice and humans indicates significant differences in the adrenal cortex biology of the opposite sex. Using genetic tools combined with hormonal treatments, Grabek et al. demonstrate that cell proliferation and cell recruitment from a capsular stem cell compartment are active in females but suppressed by androgens in male mice.